Froth flotation improvement by plasma pretreatment of sulfide minerals. (November 2017) - May, Frank; Hamann, Stephan; Quade, Antje; Brüser, Volker
Highlights: Low-temperature plasma is a powerful tool for modifying mineral surfaces. Plasma treatments allow selective oxidation of sulfide mixtures. Low-temperature plasma can improve the efficiency of froth flotation processes. Plasma treated pyrite/chalcopyrite mixtures can be separated by fatty acid collector. Plasma treated chalcopyrite/molybdenite mixtures can separated by PAX and fatty acid collector. Abstract: By implementing a low-temperature plasma pretreatment step in the processing procedure for separating different sulfide mineral mixtures, it has been possible to improve the efficiency of froth flotation. Two powder mixtures consisting of pyrite/chalcopyrite and chalcopyrite/molybdenite were selectively oxidized in an Ar/O2 microwave plasma. The oxide/sulfur mixture obtained was separated by using an oxide collector. The recovery of each mixture component was measured and the results were compared with the untreated material. For separating the pyrite/chalcopyrite mixture, high selectivity could be achieved after plasma pretreatment using the oxide collector Flotinor FS-2. One hundred percent of chalcopyrite could be recovered whilst the recovery rate of pyrite remained below eight percent. Additionally, major improvements could be achieved in the efficiency of separating the chalcopyrite/molybdenite mixtures. In all cases, it was possible to avoid the use of activating and depressant reagents, which successfully demonstrates that the surface oxidation selectivity of the plasma pretreatment ensures high flotation efficiencies by using an oxide collector to separate the sulfide mixture. Additional XPS measurements have been carried out to investigate the oxidation of the sulfide surface.